Prime-time families : television culture in postwar America - Taylor, Ella (University of California Press, 1989)
Prime-Time Families provides a wide-ranging new look at television entertainment in the past four decades. Working within the interdisciplinary framework of cultural studies, Ella Taylor analyzes television as a constellation of social practices. Part popular culture analysis, part sociology, and part American history, Prime-Time Families is a rich and insightful work the sheds light on the way television shapes our lives.